Control of muscle protein synthesis in response to exercise and amino acids - Naoya Nakai; Fuminori Kawano; Yoshinobu Ohira (Japanese Society of Physical Fitness and Sports Medicine, 2012)
There is a general consensus that resistance exercise and nutrition (especially amino acids) are the most effective interventions for maintaining skeletal muscle mass. The intracellular signaling pathways through the mammalian target of rapamycin (mTOR), a serine/threonine protein kinase, are the most established mechanism for controlling muscle protein synthesis. Acute bouts of resistance exercise and amino acid ingestion independently activate mTOR and its downstream targets that modulate protein translation initiation and elongation. Although resistance exercise can modulate protein synthesis by endocrine regulation, such as the secretion of hormones and growth factors, one of the most recognized mechanisms for controlling muscle mass by resistance exercise involves mechanical tension. In regard to nutritional regulation, recent research indicates that intracellular amino acid availability, particularly that of leucine, may be a primary regulator of muscle protein synthesis following the ingestion of amino acids. The authors previously reported that leucine catabolism also has a significant impact on amino acid-induced protein synthesis. In contrast to established downstream molecular targets such as p70 S6 kinase (p70S6K) and eukaryotic initiation factor 4E-binding protein (4E-BP1), the upstream mediators, for regulating mTOR and protein synthesis in response to resistance exercise and amino acids, remain to be clarified. In this brief review, current progress regarding the intracellular mechanisms of muscle protein synthesis, in response to resistance exercise and amino acid ingestion, is discussed.